Should the vocational quality of people with intellectual disabilities be expected? A study of interviews with employers - Zhang, Yi; Kway, Hock Eng; Gnana Piragasam, Grace Annammal (Jurnal Pendidikan Bitara UPSI, 2024)
Intellectual disabilities are the most difficult to find employment among all types of disabilities. In the public's mind, they are more in need of protection which also creates the impression that they can’t be independent. However, people with intellectual disabilities also have a desire to work. In this study, a semi-structured interview outline was used to interview six representatives of enterprises that provide jobs for intellectual disabilities, in order to understand their expectations of employees with intellectual disabilities and answer whether intellectual disabilities have the value of work. What are the vocational qualities they should possess for employment?The results show that: all respondents expressed their understanding and welcome to the employment of people with intellectual disabilities. They also believe that employees with intellectual disabilities are required to have vocational qualities, especially some vocational implicit qualities. The expectations of employees with intellectual disabilities vary from different position of representatives. Based on these findings, the study draws the following conclusions: 1. It is possible for people with intellectual disabilities to find employment to a certain extent.2. Employers have requirements and expectations on the vocational quality of people with intellectual disabilities.3. Compared with the explicit quality of vocational knowledge and skills, the implicit quality of people with intellectual disabilities is more valued by employers. 4. Vocational implicit qualities such as communication ability, emotional control ability, habit of following rules, cooperation awareness, safety awareness are emphasized.5. Vocational education is the most fundamental and effective way to cultivate the vocational quality of students with intellectual disabilities. Short-term psychological interventions are also worth trying.